The timing of work and work-family conflicts in Spain: who has a split work schedule and why? - Catalina Amuedo-Dorantes; Sara de la Rica (Institute for the Study of Labor (IZA), 2009)
Spain, as other south-Mediterranean countries, is characterized for the predominance of split work schedules. Split work schedules typically consist of 5 hours of work in the morning (typically from 9 am to 2 pm), followed by a 2 hour break and another 3 hours of work in the afternoon/evening (typically from 4 pm to 7 pm). Because of the evening work hours, split work schedules are contributing to work-family conflicts in the midst of significantly higher female labor force participation. Our purpose is to examine who has a split work schedule and why. We focus on full-time working women with full-time working partners, for whom the need to reconcile work and family responsibilities is likely to be more pressing. We first find that women with partners with a split work schedule or without children (less than 20 percent our sample) are more likely to have a split work schedule. Yet, despite the revealed preference for a continuous work schedule of the remaining women in our sample, we fail to find evidence of a compensating wage differential for having a split work schedule. We thus examine why and find that younger and less educated women more likely to be constrained in their job choices are more likely to work in the private sector, where split work schedules are primarily found.
Keywords: J16; J31; J81; 330; Work-family conflicts; timing of work; split/continuous time schedule; compensating wage differentials; job constraints; Teilzeitarbeit; Arbeitszeitflexibilisierung; Frauenerwerbstätigkeit; Familie-Beruf; Lohnstruktur; Spanien